Critique on “Investigating the Success Rate of Vaginal Delivery After Cesarean Section and Its Associated Factors in Afghan Women: Insights from a Maternity Hospital in Kabul” [Letter] - Alokozay E; Alokozay N; Tokhi E (International Journal of Women's Health, 2025)
Ehsanullah Alokozay,1,* Najibullah Alokozay,2,* Eliass Tokhi1,* 1Faculty of Medicine, Kandahar University, Kandahar, Afghanistan; 2Kabul University of Medical Science “Abu Ali Ibn Sina”, Kabul, Afghanistan*These Authors contributed equally to this workCorrespondence: Ehsanullah Alokozay, Faculty of Medicine, Kandahar University, District # 10, Kandahar, 3801, Afghanistan, Tel +93707026138, Email hebibzaiehsanullah@gmail.com